Are Further Cross Section Measurements Necessary for Space Radiation Protection or Ion Therapy Applications? Helium Projectiles - Norbury, John W.; Battistoni, Giuseppe; Besuglow, Judith; Bocchini, Luca; Boscolo, Daria; Botvina, Alexander; Clowdsley, Martha; de Wet, Wouter; Durante, Marco; Giraudo, Martina; Haberer, Thomas; Heilbronn, Lawrence; et al. (Frontiers in Physics, 2020)
The helium (4He) component of the primary particles in the galactic cosmic ray (GCR) spectrum makes significant contributions to total astronaut radiation exposure. ^4He projectile ions are also desirable for direct applications in ion therapy. They contribute smaller projectile fragmentation compared to Carbon (12C) ions and smaller lateral beam spreading compared to protons. Space radiation protection and ion therapy applications need reliable nuclear reaction models and transport codes for energetic particles in matter. Neutrons and light ions (1H, 2H, 3H, 3He, 4He) are the most important secondary particles produced in space radiation and ion therapy nuclear reactions; these particles penetrate deeply and make large contributions to dose equivalent. Since neutrons and light ions may scatter at large angles, double differential cross sections are required by transport codes that propagate radiation fields through radiation shielding and human tissue. This work will review the importance of 4He projectiles to space radiation and ion therapy, and outline the present status of neutron and light ion production cross section measurements and modeling, with recommendations for future needs.